2020
DOI: 10.1002/cjce.23908
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the microstructure of fluidized nanoparticle agglomerates by TEM image analysis

Abstract: In this paper, the hierarchical solid structures and multiscale pore structures inside fluidized nanoparticle agglomerates (FNPAs) are qualitatively revealed in the transmission electron microscope (TEM) images of ultrathin slices of solidified FNPAs from the bottom of the bed. The micromorphology of aggregates and simple agglomerates, the porosities of pores intra and inter simple agglomerates, and pore size distributions inside FNPAs are quantitatively analyzed by image analysis. The average fractal dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Moreover, it is also widely reported that the fluidized nanoparticle agglomerate possesses fractal property [ 31 ]. Many experimental observations also reveal that the distribution of pore structure inside the fluidized nanoparticle agglomerate is not uniform [ 32 ]. A physical model of a fractal porous sphere with continuously radially varying permeability was established for fractal nanoparticle agglomerates based on rigid deduction from fractal theory.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it is also widely reported that the fluidized nanoparticle agglomerate possesses fractal property [ 31 ]. Many experimental observations also reveal that the distribution of pore structure inside the fluidized nanoparticle agglomerate is not uniform [ 32 ]. A physical model of a fractal porous sphere with continuously radially varying permeability was established for fractal nanoparticle agglomerates based on rigid deduction from fractal theory.…”
Section: Methodsmentioning
confidence: 99%
“…Here d p ′ should be used instead of the diameter of the primary nanoparticles for calculating the local permeability . Based on the preliminary experimental measurements, , d p ′ is taken as 7.6 μm. This RVPM shows that for a given D f , the local permeability inside FNPAs becomes larger along the radial direction toward the outer layers.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, nanoparticles are widely utilized in multiphase flow systems for their numerous remarkable properties distinct from macroscopic materials. , The excellent combination of nanoparticles and gas–solid two-phase flow has been successfully applied to nanomaterial synthesis, coating modification, atomic deposition, photocatalytic pyrolysis, and other hot directions of industrial production. However, due to strong interparticle attraction, nanoparticles always participate in fluidization as agglomerates in dense gas–solid flows such as fluidized bed reactors, etc. , Nowadays, the self-similarity, high porosity, multistage, and inhomogeneous permeable structure of nanoparticle agglomerates has been experimentally confirmed and widely acknowledged. Nanoparticle agglomerates with self-similar properties are often known as fractal nanoparticle agglomerates (FNPAs). Due to the complex hydrodynamic conditions and the fragile structure of FNPAs, experimental information on their hydrodynamic behaviors is still rare in the literature, although some experimental studies have been conducted on the hydrodynamic behaviors of artificial permeable bodies. , With the development of computational technologies, numerical simulation provides a new and powerful way to study the detailed hydrodynamic characteristics of FNPAs.…”
Section: Introductionmentioning
confidence: 99%
“…The local permeability at the radial distance of r is obtained by the Carman–Kozeny model by Equation (): Kr=εr3dp2180()1goodbreak−εr2. Our previous study [ 34 ] and other literature [ 31 ] showed that the structures of agglomerates are built up by both aggregation and agglomeration mechanisms. From primary nanoparticles to final form, the structures have three stages, including aggregates, simple agglomerates, and fluidized agglomerates.…”
Section: Methodsmentioning
confidence: 99%